Survey of Users Interest in Initiatives Related to the European Program Healthy Lifestyle 4 All - Maria Popova-Hristova (Editura Universitatii Transilvania din Brasov, 2023)
The European Commission Healthy Lifestyle 4 All (HL4A) program aims to link sports and active lifestyles with health, food, and other policies. Healthy Lifestyle 4 All demonstrates the EC's commitment to promoting healthy lifestyles among all generations and across different social groups. HL4A is guided by the position that everyone can benefit from activities that improve health and well-being. The present study presents the attitudes of youth, corporations, and start-up companies regarding their involvement in initiatives related to the three pillars of Healthy Lifestyle 4, namely: Improved awareness of healthy lifestyles among all generations. Easy access to sports, physical activity, and healthy eating. A comprehensive holistic approach linking food, health, well-being, and sport.